Efecto de las exportaciones de metales y minerales, inversión extranjera directa y tierras cultivables en el crecimiento económico en Ecuador. - Campoverde Sanmartin., Johnny David (2020)
The Ecuadorian economy throughout history has depended to a great extent on the exploitation and commercialization of oil, with this having a participation in the GDP of 13.2% in 2011 and 7.25% in 2018; therefore, it is of vital importance to look towards other economic sectors such as mining, foreign investment and agriculture which, when boosted, can diversify and strengthen the country's economy. In this sense, the main objective of this research is to analyze the effect of metal and mineral exports, foreign direct investment and arable land on Ecuador's economic growth between 1980 and 2019, through an econometric study, in order to analyze the evolution, short and long term relationship and causality between these variables. For this reason, a time series methodology and the application of cointegration techniques were used. The World Bank's database (2020) was used to obtain annual information on each of the variables. The results obtained show that the evolution of these variables is very irregular, with large rises and sharp falls. On the other hand, using the VEC model, it was determined that there is a positive short-term relationship between foreign direct investment, arable land and economic growth, while in the long term, exports of metals and minerals, foreign direct investment and arable land have a positive impact on the Ecuadorian economy. Among the main recommendations was the reduction of taxes on technology destined for the primary sector of the economy that includes natural resources and agriculture. It is also recommended that Ecuador generate incentives such as trade agreements, reduction of bureaucracy, simplification of procedures and reduction of taxes on new investments.